2022
DOI: 10.1101/2022.10.19.512869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A histone methylation-MAPK signaling axis drives durable epithelial-mesenchymal transition in hypoxic pancreas cancer

Abstract: Here, we show that hypoxia drives especially long-lasting epithelial-mesenchymal transition (EMT) in pancreatic ductal adenocarcinoma (PDAC) primarily through a positive-feedback histone methylation-MAPK signaling axis. We find that neoplastic PDAC cells preferentially undergo EMT in hypoxic tumor regions in multiple model systems and that hypoxia drives a cell-autonomous EMT in PDAC cells which, unlike EMT in response to growth factors, can last for weeks. We further demonstrate that hypoxia reduces histone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 138 publications
1
5
0
Order By: Relevance
“…Additionally, to account for the hypoxia-specific enrichment of AXL, studies have found that HIF-1⍺ and HIF-2⍺ directly promote AXL expression, which promotes SRC activity (33). We have previously established a role for SRC-dependent MAPK/ERK-signaling in regulating hypoxiamediated EMT (3), which unifies the present study and previous findings on FAT1 and AXL to provide a mechanism for hypoxia-driven EMT in PDAC.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Additionally, to account for the hypoxia-specific enrichment of AXL, studies have found that HIF-1⍺ and HIF-2⍺ directly promote AXL expression, which promotes SRC activity (33). We have previously established a role for SRC-dependent MAPK/ERK-signaling in regulating hypoxiamediated EMT (3), which unifies the present study and previous findings on FAT1 and AXL to provide a mechanism for hypoxia-driven EMT in PDAC.…”
Section: Discussionsupporting
confidence: 85%
“…HPAF-II cells were used because they are baseline epithelial and an established model for welldifferentiated PDAC (23). As we have observed previously (3), the extent of mesenchymal transition differed between growth factors and hypoxia as EMT drivers, with hypoxia promoting vimentin expression in only a minority of cells and growth factors causing most cells to express abundant vimentin (Figure 1A). Thus, both conditions produced a heterogeneous EMT among cells but to different degrees.…”
Section: Emt Occurs Heterogeneously In Response To Growth Factors or ...mentioning
confidence: 80%
See 3 more Smart Citations